Visual And Refractive Outcomes of Myopia Astigmatism After Small Incision Lenticule Extraction (ReLEx SMILE) Procedures; Retrospective Study: Oral Presentation - Observational Study - Ophthalmologist - ANDI AKHMAD FAISAL; Nashrul Ihsan; Ucok P. Pasaribu; Vidyapati Mangunkusumo (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Small Incision Lenticule Extraction (ReLEx SMILE) is becoming more popular as a flapless and minimally invasive form of laser vision correction for the treatment of myopia and myopia astigmatism. This study aimed to assess postoperative visual and refractive outcomes of SMILE- based correction of myopia astigmatism, to evaluate the efficacy, predictability, safety, and stabilityof this procedure over a one-month postoperative period Methods : This retrospective study evaluated 200 eyes of 100 patients who underwent ReLEX SMILE technique, using the Zeiss VisuMax Laser between July 2020 and October 2022. Before surgery, 1 day and 1 month after surgery, the efficacy, predictability, safety, and stability of the procedure were assessed. Results : The preoperative Mean Uncorrected Distance Visual Acuity (UCVA) was 1.55 ± 0.53. Corrected Distance Visual Acuity (BCVA) was 20/20 or better in 74.50% and 90% of eyes in 1 day and 1 month after surgery, respectively. MRSE reduced from -5.22 ± 2.44 to -0.22 ± 0.54 at 1 day post-operative, and -0.19 ± 0.51 at 1 month. 75% of eyes had an unchanged BCVA between 1 day and 1 month after surgery. 72% of eyes achieved spherical equivalent within ±0.5 D and 94% of eyes were within ±1.0 1 month after surgery. The intraoperative complication was suction loss in two patients. Conclusion : SMILE can be considered an effective and safe refractive surgery for the treatment of myopia astigmatism.